Removal of Methylene Blue Using Used Paper Powder - Ghina Labiebah; Gunawan Gunawan; Muhammad Cholid Djunaidi; Abdul Haris; Didik Setiyo Widodo (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
Methylene blue removal by adsorption method had been done in batch method using adsorbent of used paper powder. Adsorption parameters covering adsorbent doses, contact times, pH, adsorbate concentrations and adsorption isotherm as well as desorption study of the absorbed methylene blue were evaluated. The results showed the highest adsorption of methylene blue was obtained at an optimum adsorbent dose, for 30 min at pH > 9. The maximum adsorption capacity of 30.77 mg/g was obtained with Langmuir isotherm model. While the effective methylene blue desorption on the used paper powder adsorbent was obtained c.a. 0.27 mg/g at pH 1.